Microbial fermentation and enzyme technology - Thatoi, H. N. (Boca Raton : CRC Press, 2020)
The discovery of enzymes as biocatalysts has led to various biotechnological developments. The capability of enzymes to catalyse various chemical reactions both in vivo and in vitro has led them to applications in various industries, such as food, feed, pharmaceutical, diagnostics, detergent, textile, paper, leather, and fine chemical industries. Microbial Fermentation and Enzyme Technology mainly focuses on production and application of enzymes in various industries. Further, it also discusses recent developments in enzyme engineering particularly those involved in creating and improving product formations through enzyme and fermentation technology. Salient features: Includes current research and developments in the area of microbial aspects in different fields like food, chemicals, pharmaceutical, bioprocess, etc. Discusses various enzymes that are used in refinement of environmental pollutions and its application in different industrial sectors Focuses on production and application of enzymes in various industries Highlights recent developments in enzyme engineering with respect to its application in textile, pharmaceutical, nanobiotechnology, bioremediation and many other related fields.
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Biochemistry; SCIENCE / Environmental Science; SCIENCE / Life Sciences / Biology / Microbiology; Enzymes -- Industrial applications; Fermentation; Fermentation products industry